Suicidal Ideation and its Associated Factors in Medical Students of Clinical Years at a Private Medical College of Karachi - Mansoora Jaffery; Nazia Jameel; Syed Muhammad Zulfiqar Hyder Naqvi; Sabika Jaffer (Liaquat National Journal of Primary Care)
Background: Suicide is defined as death caused by self-directed injurious behavior with any intent to die as a result of the behavior. Medical program admissions are emotionally challenging due to competition and limited spots. The demanding coursework and clinical rotations, long study hours, and sleep deprivation make medical students prone to mental health issues. Objective: To assess suicidal ideation and its associated factors in medical students of clinical years at a private medical college in Karachi, Pakistan. Methods: A cross-sectional study was conducted at Baqai Institute of Health Science, Karachi, from December 2022 to December 2023. The study population comprised clinical-year medical students of Baqai Medical College, Karachi. Suicidal ideation was assessed using the SENTIA suicidal behavior assessment scale. Inferential analysis was performed using the Mann-Whitney U test, Kruskal Wallis H test, and multiple linear regression. Results: A total of 252 medical students were approached out of which 237 participated in the study. The mean and standard deviation of the age of the respondents was 22.4±1.24 years and 137 (58%) of them were females. Moreover, the total suicidal ideation score and that of subscale suicidal ideation were significantly different across categories of marital status (p=0.026 and p=0.007 respectively) whereas that of subscale suicidal act/planning was significantly different across categories of both marital status (p=0.30) and family type (p=0.047). None of the patient features was found to be associated with suicidal ideation in regression analysis. Conclusion: Suicidal ideation scores were found to be significantly associated with the marital status and family type of the students on bivariate analysis. Students who are divorced, widowed, separated, or living in a joint family system should be monitored vigilantly and provided with appropriate counseling by a professional counselor if the need arises.